Relato de caso clínico: condiloma acuminado oral e suas considerações sobre diagnóstico e tratamento - Moda, Mariana Dias [UNESP] (2011)
The oral acuminatum condyloma is a sexually transmissible infection caused by human papillomavirus, although there is a lower possibility of transmission during delivery through the skin, by self-inoculation and in immune compromised individuals. The importance of diagnosing this type of injury is based on the oncogenic potential for some types of HPV, including the mouth. This paper reports the clinical case of female patient, 72 years old presenting this type of lesion in the left buccal mucosa. The different methods of diagnosis and the different forms of treatment vary depending on the size, location and characteristics of each lesion, which were covered in this paper